2017
DOI: 10.3892/ol.2017.7203
|View full text |Cite
|
Sign up to set email alerts
|

Novel combination of paraspinal keyhole surgery with a tubular retractor system leads to significant improvements in lumbar intraspinal extramedullary schwannomas

Abstract: The aim of the present study was to investigate the efficacy of combining paraspinal keyhole surgery with a tubular retractor system for the microsurgical removal of lumbar intraspinal extramedullary schwannomas. A retrospective analysis was conducted of 56 patients with lumbar intraspinal extramedullary schwannomas who were treated using the microsurgical paraspinal keyhole approach with a tubular retractor system. The mean ± standard deviation was calculated for the following parameters: Surgery time (96.21±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…Since then, the results of multiple randomised controlled trials (RCTs) and systematic reviews12–15 comparing the efficacy of tubular microdiscectomy (TMD) and CMD have revealed no significant difference between the two. Recently, Zhuang et al and Chunmei et al 16 17 improved on the tubular retractors and trocar systems and introduced the paraspinal minitubular microdiscectomy system (PMTM). PMTM is characterised by a smaller tubular diameter which can achieve bilateral decompression based on the surgical approach from one side.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the results of multiple randomised controlled trials (RCTs) and systematic reviews12–15 comparing the efficacy of tubular microdiscectomy (TMD) and CMD have revealed no significant difference between the two. Recently, Zhuang et al and Chunmei et al 16 17 improved on the tubular retractors and trocar systems and introduced the paraspinal minitubular microdiscectomy system (PMTM). PMTM is characterised by a smaller tubular diameter which can achieve bilateral decompression based on the surgical approach from one side.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously performed intraspinal subdural schwannoma and thoracic dumbbell tumor resections using the microtubular technique, and we have also attempted lumbar dumbbell tumor resection under spinal endoscopy. 9,15,16 For Eden type III-IV lumbar tumors with a single segment and a maximum diameter of < 5 cm, both PTET and PAMT achieved 1-stage total resection. In PTET approach, the tumor resection procedure extends from the paravertebral tumor to the intraspinal canal tumor.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Zhuang et al further concluded that the MIS surgery with tubular retractor allowed more functional improvement and pain reduction at postoperative 6 months. 25 En bloc resection of the intradural extramedullary spinal tumor with its dural attachment theoretically achieves the best oncological outcome. However, a hard tumor consistency, ventral site of dural attachment, and poor arachnoid plane often limit en bloc resection.…”
Section: Discussionmentioning
confidence: 99%